Pre-transplant Type 2 Diabetes Mellitus Is Associated With Higher Graft Failure and Increased 5-Year Mortality After Heart Transplantation - Rivinius, Rasmus; Gralla, Carolin; Helmschrott, Matthias; Darche, Fabrice F.; Ehlermann, Philipp; Bruckner, Tom; Sommer, Wiebke; Warnecke, Gregor; Kopf, Stefan; Szendroedi, Julia; Frey, Norbert; Kihm, Lars P. (Frontiers in Cardiovascular Medicine, 2022)
Aims: Cardiac transplant recipients often suffer from type 2 diabetes mellitus (T2DM) but its influence on graft failure and post-transplant mortality remains unknown. The aim of this study was to investigate the long-term effects of pre-transplant T2DM in patients after heart transplantation (HTX). Methods: This study included a total of 376 adult patients who received HTX at Heidelberg Heart Center between 01/01/2000 and 01/10/2016. HTX recipients were stratified by diagnosis of T2DM at the time of HTX. Patients with T2DM were further subdivided by hemoglobin A1c (HbA1c ≥ 7.0%). Analysis included donor and recipient data, immunosuppressive drugs, concomitant medications, post-transplant mortality, and causes of death. Five-year post-transplant mortality was further assessed by multivariate analysis (Cox regression) and Kaplan–Meier estimator. Results: About one-third of all HTX recipients had T2DM (121 of 376 [32.2%]). Patients with T2DM showed an increased 5-year post-transplant mortality (41.3% versus 29.8%; P = 0.027) and had a higher percentage of death due to graft failure (14.9% versus 7.8%; P = 0.035). Multivariate analysis showed T2DM (HR: 1.564; 95% CI: 1.054–2.322; P = 0.026) as an independent risk factor for 5-year mortality after HTX. Kaplan–Meier analysis showed a significantly better 5-year post-transplant survival of patients with T2DM and a HbA1c < 7.0% than patients with T2DM and a HbA1c ≥ 7.0% (68.7% versus 46.3%; P = 0.008) emphasizing the clinical relevance of a well-controlled T2DM in HTX recipients. Conclusions: Pre-transplant T2DM is associated with higher graft failure and increased 5-year mortality after HTX.